Exploring the Association Between the Doppler Findings of Endometriomal Wall Vascularization and Volume of the Endometrioma - Berna Seçkin; Ayla Sargın Oruç; Yunus Yıldız; Mustafa Uğur (Medical Network, 2016)
OBJECTIVE: To assess the relationship between vascularity patterns along the endometriomal wall assessed by Doppler ultrasound and volume of the endometrioma. STUDY DESIGN: A total of 58 patients who underwent laparoscopic surgery for ovarian endometrioma were evaluated for volume and vascularization by color and power Doppler ultrasonography before the surgery. The presence and amount of blood flow reported in terms of color scale and pulsed Doppler indiceswere examined. Endometriomal volume in patients with different amount of blood flow (avascularor scantily vascularized group; n= 42 and moderately or highly vascularized group; n=16) was compared and the relation of volume to Doppler indices was assessed by Spearman's correlation analysis. p<0.05 was considered statistically significant. RESULTS: No differences were found with regard to the volume between avascular or scantily vascularized endometriomas and moderately or highly vascularized endometriomas (p=0.41). But, the volume of the endometrioma was positively correlated with the PI and RI values (Spearman's r =0.335 and r=0.382, respectively), and the correlation was statistically significant for both PI and RI (p=0.026 and p=0.011, respectively). CONCLUSION: We could not demonstrate a significant association between endometriomal volume and amount of blood flow along the endometrioma wall. However, the increased volume of endometrioma is found to be correlated with high vascular resistance, thus decreased vascularization compared to smaller endometriomas assessed by pulsed Doppler indices. This finding may aid in the development of adjuvant treatments for patients with smaller endometriomas and lower resistance to blood flow.